Quelles pratiques enseignantes pour favoriser l’inclusion scolaire des élèves nouveaux arrivants dans des classes d’accueil au primaire ? - Koubeissy, Rola (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
This article focuses on teaching practices that promote the academic inclusion of newly arrived immigrant students who attend elementary welcoming classes in Quebec. Data was collected through comprehensive interviews with four teachers working in different schools. For a better understanding of the teachers’ practices, we carried out a cross-sectional analysis based on two themes: the teachers’ perceptions of reception classes and inclusion, and the practices mobilized to promote student inclusion. The findings reveal, among other things, that the teachers share a positive perception of welcoming classes and of inclusion, and that they are aware of the importance of (re)cognizing their students’ realities and experiences. However, they express a sense of frustration regarding the challenges they face, most notably the isolation of their classes and students and the forms of exclusion they themselves experience. These findings give a dual meaning to inclusion: include in order to promote students’ learning and include to counter the school exclusion faced by these students.